Netrin1-DCC-Mediated Attraction Guides Post-Crossing Commissural Axons in the Hindbrain - Shoja-Taheri, Farnaz (J Neurosci, 2015)
Commissural axons grow along precise trajectories that are guided by several cues secreted from the ventral midline. After initial attraction to the floor plate using Netrin1 activation of its main attractive receptor, DCC (deleted in colorectal cancer), axons cross the ventral midline, and many turn to grow longitudinally on the contralateral side. After crossing the midline, axons are thought to lose their responsiveness to Netrin1 and become sensitive to midline Slit-Robo repulsion. We aimed to address the in vivo significance of Netrin1 in guiding post-crossing axon trajectories in mouse embryos. Surprisingly, in contrast to the spinal cord, Netrin1 and DCC mutants had abundant commissural axons crossing in the hindbrain. In Netrin1 and DCC mutants, many post-crossing axons made normal turns to grow longitudinally, but projected abnormally at angles away from the midline. In addition, exposure of cultured hindbrain explants to ectopic Netrin1 caused attractive deflection of post-crossing axons. Thus, Netrin1-DCC signaling is not required to attract pre-crossing axons toward the hindbrain floor plate, but is active in post-crossing guidance. Also in contrast with spinal cord, analysis of hindbrain post-crossing axons in Robo1/2 mutant embryos showed that Slit-Robo repulsive signaling was not required for post-crossing trajectories. Our findings show that Netrin1-DCC attractive signaling, but not Slit-Robo repulsive signaling, remains active in hindbrain post-crossing commissural axons to guide longitudinal trajectories, suggesting surprising regional diversity in commissural axon guidance mechanisms. SIGNIFICANCE STATEMENT The left and right sides of the brainstem and spinal cord are connected primarily by axon fibers that grow across the ventral midline, and then away on the other side to their targets. Based on spinal cord, axons are initially attracted by diffusible attractive protein signals to approach and cross the midline, and then are thought to switch to repulsive cues to grow away on the opposite side. Our results in the hindbrain show that the major midline attractant, Netrin1, is not required for midline crossing. However, the post-crossing axons depend on Netrin1 attraction to set their proper trajectories on the other side. Overall, these findings suggest that commissural axons use distinct mechanisms to navigate in different CNS regions.